2021
DOI: 10.3389/fncel.2021.689332
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin and the Synapse

Abstract: Huntington disease (HD) is a monogenic disease that results in a combination of motor, psychiatric and cognitive symptoms. HD is caused by a CAG trinucleotide repeat expansion in the huntingtin (HTT) gene, which results in the production of a pathogenic mutant HTT protein (mHTT). Although there is no cure at present for HD, a number of RNA-targeting therapies have recently entered clinical trials which aim to lower mHTT production through the use of antisense oligonucleotides (ASOs) and RNAi. However, many of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 188 publications
(281 reference statements)
1
43
0
Order By: Relevance
“…There is ample evidence to suggest that subtle alterations of synapses occur before overt neuronal death, and that these changes are predictive of the onset of behavioral problems associated with HD ( Morton et al, 2001 ; Li H. et al, 2003 ; Joshi et al, 2009 ; Raymond et al, 2011 ). Huntingtin is highly expressed in the presynaptic terminals of nerve cells ( DiFiglia et al, 1995 ), and various proteins that regulate both the presynaptic and postsynaptic function have been shown to interact with HTT ( Li et al, 2002 ; Li J. Y. et al, 2003 ; Barron et al, 2021 ). These proteins affect a range of pre and postsynaptic functions, including endocytosis, synaptic homeostasis, and axonal transport on the presynaptic side, and postsynaptic receptor localization and dendritic protein transport at the post-synapse.…”
Section: Mutant Huntingtin Causes Early Synaptic Dysfunction In Hunti...mentioning
confidence: 99%
“…There is ample evidence to suggest that subtle alterations of synapses occur before overt neuronal death, and that these changes are predictive of the onset of behavioral problems associated with HD ( Morton et al, 2001 ; Li H. et al, 2003 ; Joshi et al, 2009 ; Raymond et al, 2011 ). Huntingtin is highly expressed in the presynaptic terminals of nerve cells ( DiFiglia et al, 1995 ), and various proteins that regulate both the presynaptic and postsynaptic function have been shown to interact with HTT ( Li et al, 2002 ; Li J. Y. et al, 2003 ; Barron et al, 2021 ). These proteins affect a range of pre and postsynaptic functions, including endocytosis, synaptic homeostasis, and axonal transport on the presynaptic side, and postsynaptic receptor localization and dendritic protein transport at the post-synapse.…”
Section: Mutant Huntingtin Causes Early Synaptic Dysfunction In Hunti...mentioning
confidence: 99%
“…Among these functions, HTT regulates neurogenesis and brain development, together with the survival and function of cortical and striatal neurons in the adult brain [ 8 , 9 ]. Molecularly, HTT scaffolds a large repertoire of binding proteins to coordinate several cellular processes, including gene transcription, synaptic activity, vesicles trafficking and autophagy [ 8 10 ]. In spite of this knowledge, the contribution of the non-pathogenic CAG tract itself and its highly polymorphic lengths in normal HTT function remains poorly examined.…”
Section: Introductionmentioning
confidence: 99%
“…This, however, stresses the need for further understanding of the function of normal HTT in cells. Several in vitro and in vivo studies showed that normal HTT is involved in numerous cellular processes, including cell maturation, vesicle trafficking, synaptic transmission, and neuroprotection (reviewed in [7][8][9][10]). Additionally, further knowledge about how gains-or losses-ofdysfunctional mHTT affects the various tissues and cell types throughout the body is needed.…”
Section: Introductionmentioning
confidence: 99%